2020
DOI: 10.26803/ijlter.19.8.14
|View full text |Cite
|
Sign up to set email alerts
|

High School Students’ Difficulties in Making Mathematical Connections when Solving Problems

Abstract: The primary purpose of studying mathematics is that students can solve problems, both mathematical and real-life problems. In this way, mathematical connections play an essential role in enabling students to solve mathematical problems. Students' difficulties in mathematical connections can cause difficulties in solving problems. This study aims to describe the mathematical connections difficulties experienced by students when solving mathematical problems. This study is qualitative with a phenomenological app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…The two difficulties, namely mathematical reasoning, and mathematical connections, resulted in students not being able to solve the problem of the area of the fish pond. This fact is in accordance with the results of the study that most students have difficulty making mathematical connections which result in students' difficulties in solving problems (Jailani, Retnawati, Apino, & Santoso, 2020) . This shows that there is a relationship between mathematical reasoning abilities, and mathematical connections with mathematical problem-solving abilities.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The two difficulties, namely mathematical reasoning, and mathematical connections, resulted in students not being able to solve the problem of the area of the fish pond. This fact is in accordance with the results of the study that most students have difficulty making mathematical connections which result in students' difficulties in solving problems (Jailani, Retnawati, Apino, & Santoso, 2020) . This shows that there is a relationship between mathematical reasoning abilities, and mathematical connections with mathematical problem-solving abilities.…”
supporting
confidence: 91%
“…Mathematical connection ability is the ability to relate various mathematical objects, and between mathematics and things outside mathematics which is measured based on the following indicators: 1) connecting contexts in everyday life and mathematics (Y4); 2) determine the relationship between mathematical objects used in answering questions (Y5); and 3) utilizing the relationship between mathematical objects to answer the given question (Y6) (NCTM, 2000) (Putri & Wutsqa, 2019) (Pambudi et al, 2020) (Hasbi et al, 2019) (Kadir et al, 2020) (Jailani et al, 2020).…”
mentioning
confidence: 99%
“…The investigation on test item difficulty has also indicated the struggle of students in solving problems that required them to make and use mathematical connections, especially intra-mathematical connections. Because García-García and Dolores-Flores (2018) argued that there is a strong relationship between understanding and connections, and it was supported by the results of study performed by Jailani et al (2020), we encourage teachers to focus more on promoting students' mathematical understanding. Taking the results of previous study which found that unfamiliarity towards problems that require mathematical connections leads them to have difficulties in solving the problems (Jailani et al, 2020) into account, the teachers are suggested to present mathematical and application problems, in which through such problems and the process of finding the solutions to the problems, students are facilitated to make intra-mathematical connections (García-García & Dolores-Flores, 2020).…”
Section: Implications For Mathematics Learning Practicementioning
confidence: 77%
“…A previous study conducted by Yusron et al (2020) has shown similar results that problems that require mathematical connections became the most difficult among items contained in tests used in national-standardized school examinations. Jailani et al (2020) also found that most senior high school students were still struggling in making connections between mathematical representations, concepts, and procedures. In addition, Sampouw and Retnawati (2020) found two interesting results through their study.…”
Section: Discussionmentioning
confidence: 95%
“…As a result, they developed a better and more thorough understanding of topics. An implication was observed that one of the reasons for the difficulty of high school students in connecting mathematics to solving problems was the lack of reasoning skills (Jailani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%